Impact of urban atmospheric environment on hospital admissions in the elderly Impacto del ambiente atmosférico urbano en las internaciones hospitalarias de ancianos Impacto do ambiente atmosférico urbano nas internações hospitalares de idosos - Edelci Nunes da Silva; Helena Ribeiro (Universidade de São Paulo, 2012)
OBJECTIVE: To analyze the impact of intra-urban atmospheric conditions on circulatory and respiratory diseases in elder adults. METHODS: Cross-sectional study based on data from 33,212 hospital admissions in adults over 60 years in the city of São Paulo, southeastern Brazil, from 2003 to 2007. The association between atmospheric variables from Congonhas airport and bioclimatic index, Physiological Equivalent Temperature, was analyzed according to the district's socioenvironmental profile. Descriptive statistical analysis and regression models were used. RESULTS: There was an increase in hospital admissions due to circulatory diseases as average and lowest temperatures decreased. The likelihood of being admitted to the hospital increased by 12% with 1ºC decrease in the bioclimatic index and with 1ºC increase in the highest temperatures in the group with lower socioenvironmental conditions. The risk of admission due to respiratory diseases increased with inadequate air quality in districts with higher socioenvironmental conditions. CONCLUSIONS: The associations between morbidity and climate variables and the comfort index varied in different groups and diseases. Lower and higher temperatures increased the risk of hospital admission in the elderly. Districts with lower socioenvironmental conditions showed greater adverse health impacts. OBJETIVO: Analizar los efectos de las condiciones climáticas intra-urbanas en las enfermedades circulatorias y respiratorias en ancianos. MÉTODOS: Estudio transversal con 33.212 internaciones hospitalarias de ancianos en la ciudad de Sao Paulo, Sudeste de Brasil. Las variables atmosféricas colectadas en el aeropuerto de Congonhas y el índice bioclimático Physiological Equivalent Temperature fueron analizados según el perfil socioeconómico del vecindario. Se utilizaron análisis estadístico descriptivo y modelos de regresión. RESULTADOS: Hubo aumento en las internaciones por enfermedades circulatorias al disminuir las temperaturas promedio y mínima. La probabilidad de internaciones fue 12% mayor con la disminución de 1°C en el índice bioclimático y con el aumento de 1°C en las temperaturas máximas en el grupo con peor perfil socioeconómico. Hubo riesgo aumentado de internaciones respiratorias por la nociva calidad del aire en distritos con mejor perfil socioeconómico. CONCLUSIONES: Asociaciones entre morbilidad, variables climáticas e índice de conforto no presentaron patrón de comportamiento entre los diferentes grupos y enfermedades. Disgustos por el frio y calor extremo representaron mayor riesgo para internaciones de ancianos. Distritos con peores condiciones sociales y ambientales presentaron mayores impactos en la salud. OBJETIVO: Analisar o impacto das condições climáticas intra-urbanas nas doenças circulatórias e respiratórias em idosos. MÉTODOS: Estudo transversal baseado em 33.212 internações hospitalares de idosos na cidade de São Paulo, SP, de 2003 a 2007. As variáveis atmosféricas coletadas no aeroporto de Congonhas e o índice bioclimático Physiological Equivalent Temperature foram analisados segundo o perfil socioeconômico da vizinhança. Análise estatística descritiva e modelos de regressão foram usados. RESULTADOS: Houve aumento nas internações por doenças circulatórias quando houve diminuição nas temperaturas médias e mínimas. A probabilidade de internações foi 12% maior com diminuição de 1ºC no índice bioclimático e com aumento de 1ºC nas temperaturas máximas no grupo com pior perfil socioeconômico. Houve risco aumentado de internações respiratórias durante má qualidade do ar em distritos com melhor perfil socioeconômico. CONCLUSÕES: Associações entre morbidade, variáveis climáticas e índice de conforto não apresentaram padrão de comportamento entre os diferentes grupos e doenças. Desconforto para o frio e extremo de calor representaram maior risco para internações de idosos. Distritos com piores condições sociais e ambientais apresentaram maiores impactos à saúde.